2019
DOI: 10.1080/03098265.2019.1599330
|View full text |Cite
|
Sign up to set email alerts
|

Learning by doing: enhancing hydrology lectures with individual fieldwork projects

Abstract: Hydrology teaching deals with processes happening outside the classroom, which calls for active-learning methods to complement lectures. In a geography undergraduate course, new teaching methods and assessment were designed, in which students investigated a river of their choice by completing homework tasks and presenting their results on a poster. During a 3-year implementation process, the changes were evaluated using a combination of formal and informal student and lecturer feedback. Students mentioned that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
9
0
2
Order By: Relevance
“…Several studies indicate that students feel positive emotions such as enjoyment (Kern & Carpenter, 1984 ; Scott et al, 2019 ; Van Loon, 2019 ) during field‐based instruction. However, other research has found that students can also express negative emotions during field instruction such as frustration (Baum et al, 2012 ), boredom (Goulder et al, 2013 ; Orion & Hofstein, 1994 ), and even fear (Brenner et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that students feel positive emotions such as enjoyment (Kern & Carpenter, 1984 ; Scott et al, 2019 ; Van Loon, 2019 ) during field‐based instruction. However, other research has found that students can also express negative emotions during field instruction such as frustration (Baum et al, 2012 ), boredom (Goulder et al, 2013 ; Orion & Hofstein, 1994 ), and even fear (Brenner et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Past surveys and reviews on education in hydrology at the university level revealed that teachers may use multiple didactic techniques and approaches but visiting catchments with classes is still rare (Thompson et al, 2012; Wagener et al, 2007). Recent experiences of field work with students reported that “learning by doing” helped them to better understand the theory, to improve their skills, and to more effectively select and present information (Van Loon, 2019). Taking students to the field, where real hydrological processes occur, guiding them to visit monitoring equipment, making them perform simple measurements and data collection, asking them why certain approaches have been adopted and what could have been done differently, and leading them to observe the current and past signature of water on the landscape generate curiosity and engagement, stimulate questions, contribute to developing critical thinking thus opening enormous learning possibilities.…”
Section: Why Keep Experimental Catchments Alivementioning
confidence: 99%
“…While classroom lectures are typically lecturer‐centered (students are more passive), field courses invite active‐learning methods (Hakoun et al 2013; Lyon et al 2013; Van Loon 2019). Active‐learning courses are student‐centered as the instructor acts as a “facilitator” as the students “learn by doing” (Pathirana et al 2012), that is, students collect, analyze, and interpret data.…”
Section: Advances In Teaching Hydrogeology In the Fieldmentioning
confidence: 99%